2016
DOI: 10.1071/an15487
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic potential of forages consumed throughout the year by cattle in a Sahelian pastoral area

Abstract: Methane (CH4) emission from ruminants in African pastoral systems may be affected by intake and type of plants, which vary highly between rainy and dry seasons. In each of two sites located in the semiarid Sahelian area of Senegal, three Gobra zebus were monitored throughout 1 year. A representative sample of their diet was obtained once every month. Diet was mainly composed of grasses, herbaceous legumes, tree and shrub foliage and pods, and dried forage residues. CH4 production and volatile fatty acid (VFA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…gayana. These results correspond with results reported by Gemeda and Hassen (2014) and Doreau et al (2016) who reported a positive correlation between CH4 production, cell wall contents and IVOMD of forages. Digitaria eriantha had the lowest average in vitro CH4 production after the 24 and 48 hour incubation periods and tended to have a lower CH4: TGP compared to other C4 species (Table 6) in the present trial.…”
Section: Gas Productionsupporting
confidence: 92%
“…gayana. These results correspond with results reported by Gemeda and Hassen (2014) and Doreau et al (2016) who reported a positive correlation between CH4 production, cell wall contents and IVOMD of forages. Digitaria eriantha had the lowest average in vitro CH4 production after the 24 and 48 hour incubation periods and tended to have a lower CH4: TGP compared to other C4 species (Table 6) in the present trial.…”
Section: Gas Productionsupporting
confidence: 92%
“…In vitro fermentation has been proven to be a successful method for the screening of forage fermentation characteristics and methanogenic potential 12,13 . The advanced, fully automated in vitro gas production (IVGP) technique has been widely used to measure the rate and extent of fermentation of a large number of feed samples 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the absence of reliable information on livestock in the SSA region, the IPCC Guidelines suggest that the uncertainty of enteric fermentation emission factors ranges from ±30% to ±50% for Tier 1 and ± 20% for Tier 2 approaches, respectively [5]. Hence, the use of a Tier 2 approach may enable a decrease in the uncertainty of predicted enteric methane emission factors used in national GHG inventories [53][54][55]. In Senegal, the third GHG emission inventory was submitted to the UNFCCC in 2015 (see https://unfccc.int/documents/89618).…”
Section: Moving To a Tier 2 Enteric Methane Emission Factormentioning
confidence: 99%
“…The composition of fodder consumed by ruminants is well documented in Senegal, and the profile of organic matter digestibility (OMd) is available [13][14][15]54]. However, there is a need to determine at the national scale, an average value for OMd which takes into consideration seasonality.…”
Section: Importance Of Input Parametersmentioning
confidence: 99%